IMPLEMENTATION OF CRIMINAL SANCTIONS AGAINST PERPETRATORS OF BANK ACCOUNT DATA THEFT THAT IS FAIR FOR THE PUBLIC - Belgradoputra, Raden Jossy Sutari; Haryono, Waty Suwarty; Wirogioto, Ali Johardi (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
The implementation of criminal sanctions against skimming offenders must be based on principles of justice that encompass the interests of victims, society, and offenders. This crime often results in significant financial losses and psychological impacts on victims, making it essential for the penalties imposed to reflect the extent of the harm caused. The theory of justice proposed by Gustav Radbruch, namely legal justice, social justice, and substantive justice, serves as a critical foundation for enforcing the law proportionally. Legal justice enforcement, as outlined in Articles 30 and 36 of the ITE Law, provides a framework to prosecute offenders with a maximum penalty of 12 years of imprisonment and fines up to IDR 12 billion. This ensures legal certainty while also deterring potential offenders. Social justice emphasizes collective protection for society, including safeguarding banking data. The state must ensure that banking systems have secure infrastructure so that the public is less vulnerable to cybercrime. Firm punishment of offenders also instills a sense of security in the community. Substantive justice must be realized by restoring victims' losses. Punishment for offenders should not only involve imprisonment but also include mechanisms for restitution to recover victims’ material losses. Integrating these three principles ensures that the implementation of criminal sanctions is not merely repressive but also restores a sense of justice in society. This approach is necessary to maintain a balance between punishing offenders, protecting society, and upholding the rights of victims.